Firms, sorting, and the immigrant–native earnings gap - Benoit Dostie (IZA World of Labor, 2022)
Recent research has tried to quantify how firms contribute to the immigrant–native earnings gap. Findings from several countries show that around 20% of the gap is due to firm policies that lead to a systematic underrepresentation of immigrants at higher-paying firms. Results also show that some of the closing of the gap over time is attributable to the reallocation of immigrants toward higher-paying employers. This pattern is especially pronounced for immigrants coming from disadvantaged countries, who face several barriers at initial entry, including language difficulties and lack of recognition of their educational credentials.
Keywords: J3; J6; J2; J24; 330; immigrants; earnings; workers; firms; sorting; human capital